Musculoskeletal disorders among dental assistants: a cross-sectional study - Mohammad Aljanakh (BMC Musculoskeletal Disorders, 2024)
Abstract Background This study aims to investigate the prevalence of musculoskeletal disorders (MSDs) and associated sociodemographic and work-related factors among dental assistants (DAs) in the hail province, Saudi Arabia. Methods Participants were 119 DAs with an average age of 28.9 years (SD ± 4.8 years), of whom 86.6% were females. A self-administered questionnaire which included Nordic Musculoskeletal questionnaire and questions on socio-demographic and work-related factors was used. Descriptive statistics were used to calculate the prevalence of MSDs during the past 12 months and 7 days. Multivariate binary logistic regression statistical tests were used to calculate the association between MSDs and socio-demographic and work-related factors. Results The overall prevalence of MSDs among DAs was significantly high, with 85.7% reporting symptoms during the past 12 months and 47.9% during the past 7 days. The shoulders, followed by the lower back, were the most common complaints among participants in the past 12 months and 7 days, followed by the upper back and neck. Multivariate binary logistic regression analysis results show significant associations between MSDs and age, Body-Mass-Index (BMI), physical demands during working hours, work environment and posture awareness, and years of experience. Conclusions The prevalence of MSDs among DAs is high, and sociodemographic and work-related factors play an important role in exacerbation of MSDs in DAs.